SITUATION OF IMPLEMENTATION SAFETY OF NURSES AND MIDWIVES AT DIRECT DISTRICT HEALTH CENTERS BEFORE AND IMPROVEMENT AFTER TRAINING IN 2020 (Vietnam Journal of Community Medicine, 2022)
Objective: Actual situation of safe injection before and after training of Nurses - Midwives and some related factors at Nam Truc Medical Center, Nam Dinh 2020. Research Methods: An interventional cross-sectional descriptive study. Result: Descriptive study on safe injection practices according to 17 safety standards  of the Ministry of Health in 5 clinical departments at Nam Truc District Health Center. Methods: Cross sectional description. 60 Nurses - Midwives were selected to administer injections/infusions and were assessed by a checklist. Each Nurse - Midwife performed 2 injections/infusion before training and 2 injections/infusion after training, showing that: before training, there were 82 injections/infusion of safe injection standards, reaching 68.3% and 38 failed nose accounted for 31.7%. After the training, there were 108 injections/infusion that met 90% of the injection safety standards and 12 failed injections, accounting for 10%. The study also showed an improvement in the rate of safe injections for highly qualified Nurses - Midwives. People with working experience from 5 to 20 years have the highest rate of safe injections and infusions.Conclusion: The safe injection practice of clinical nurses - midwives at the district health center according to the safe injection standards of the Ministry of Health reached 68.3%, 90% after training.
Keywords: Safe injection, nursing.